Implementasi Sistem Penggajian Karyawan Berbasis Web Menggunakan Metode RAD - Munaldi (Prodi Teknik Informatika Universitas Pasir Pengaraian, 2025)
In today's digital era, many companies face challenges in managing the employee payroll system which is still done manually. PT. Tryuasda Megah Warna, as one of the companies engaged in the industry, has difficulties in managing employee attendance and payroll data. The manual process that is carried out causes inaccuracies in data, delays in payroll, and difficulties in reporting that have an impact on employee satisfaction and the company's operational efficiency. Therefore, a system is needed that can automate and simplify the payroll process. The purpose of this study is to design and implement a web-based employee payroll system that can improve the accuracy, speed, and ease of payroll data management at PT. Tryuasda is a majestic color. The method used in this study is Rapid Application Development (RAD), which allows rapid system development by involving users in every stage of development. With this approach, the prototype of the system is developed and tested iteratively, so that it can better meet the needs of the user. The results of this study show that the implemented payroll system has succeeded in increasing the efficiency of the payroll process by up to 40%, reducing data errors by up to 30%, and increasing employee satisfaction with the payroll process. In addition, this system also provides convenience in reporting and analyzing payroll data, which was previously an obstacle for management. Thus, this research not only provides solutions to existing problems, but also contributes to increasing productivity and employee satisfaction at PT. Tryuasda is a majestic color